24-epibrassinolide and 20-hydroxyecdysone affect photosynthesis differently in maize and spinach - Rothová, Olga; Holá, Dana; Kočová, Marie; Tůmová, Lenka; Hnilička, František; Hniličková, Helena; Kamlar, Marek; Macek, Tomáš (Steroids, 2014)
The aim of the work was to examine the effect of brassinosteroid (24-epibrassinolide; 24E) and ecdysteroid (20-hydroxyecdysone; 20E) on various parts of primary photosynthetic processes in maize and spinach. Additionally, the effect of steroids on gaseous exchange, pigment content and biomass accumulation was studied. The efficiency of the photosynthetic whole electron-transport chain responded negatively to the 24E or 20E treatment in both species, but there were interspecific differences regarding Photosystem (PS) II response. A positive effect on its oxygen-evolving complex and a slightly better energetical connectivity between PSII units were observed in maize whereas the opposite was true for spinach. The size of the pool of the PSI end electron acceptors was usually diminished due to 24E or 20E treatment. The treatment of plants with 24E or 20E applied individually positively influenced the content of photosynthetic pigments in maize (not in spinach). On the other hand, it did not affect gaseous exchange in maize but resulted in its reduction in spinach. Plants treated with combination of both steroids mostly did not significantly differ from the control plants. We have demonstrated for the first time that 20E applied in low (10nM) concentration can affect various parts of photosynthetic processes similarly to 24E and that brassinosteroids regulate not only PSII but also other parts of the photosynthetic electron transport chain - but not necessarily in the same way.
Keywords: listy rostlin; Brassinosteroids; Plant Proteins; Photosynthesis; Plant Leaves; Photosystem II Protein Complex; fotosyntéza; Spinacia oleracea; kukuřice setá; steroidy heterocyklické; fotosystém II (proteinový komplex); rostlinné proteiny; oxidace-redukce; ekdysteron; Oxidation-Reduction; Steroids, Heterocyclic; Zea mays; Ecdysterone; brassinosteroidy